Quorum sensing in aeromonas species isolated from patients in Malaysia - Chan, Kok Gan; Puthucheary, Savithri Devi; Chan, Xin Yue; Yin, Wai Fong; Wong, Cheng Siang; Too, Wah Seng See; Chua, Kek Heng (2011)
Bacterial quorum sensing signal molecules called N-acylhomoserine lactone (AHL) controls the expression of virulence determinants in many Gram-negative bacteria. We determined AHL production in 22 Aeromonas strains isolated from various infected sites from patients (bile, blood, peritoneal fluid, pus, stool and urine). All isolates produced the two principal AHLs, N-butanoylhomoserine lactone (C4-HSL) and N-hexanoyl homoserine lactone (C6-HSL). Ten isolates also produced additional AHLs. This report is the first documentation of Aeromonas sobria producing C6-HSL and two additional AHLs with N-acyl side chain longer than C(6). Our data provides a better understanding of the mechanism(s) of this environmental bacterium emerging as a human pathogen.